Fine Needle Aspiration Biopsy as A Useful Diagnostic Adjunct in The Management of Ameloblastoma: A Cytology Case Report - Rum Affida Rasfa; Shinta Ayu Intan; Noza Hilbertina; Meta Zulyati Oktora (Scientific Journal, 2025)
Background: Ameloblastoma is one of the most common benign odontogenic tumors, known for its slow growth but locally invasive behavior, often leading to extensive bone destruction if not diagnosed and treated early. Preoperative diagnosis of ameloblastoma can be made by Fine Needle Aspiration Biopsy (FNAB) which is used as a guide for surgical planning. Diagnosis of ameloblastoma from cytology is challenging due to many pitfalls and differential diagnosis with other odontogenic lesions, but proper sampling and accurate diagnosis are very useful inpatient management Understanding its cytomorphological features can greatly assist in early differentiation from other maxillofacial neoplasms. This case report aims to describe the appearance of ameloblastoma on FNAB and reveal the contribution of the FNAB examination in the preoperative diagnosis of ameloblastoma so that adequate surgery can be carried out and the results are more optimal. Case report: We report a case of a tumor in the mandible of a 16-year-old man with a diagnosis of right mandibular tumor. The patient was sent for FNAB to the anatomical pathology laboratory. Preoperative cytology examination showed benign odontogenic lesions indicating ameloblastoma from FNAB. Furthermore, tumor resection was performed on the patient and histopathology tissue examination was performed with results consistent with ameloblastoma. Discussion: The FNAB procedure can be performed to establish for a pre-operative diagnosis of ameloblastoma. Cytological characteristics of ameloblastoma include basaloid cells or epithelial cells resembling ameloblasts with nuclei arranged palisade at the periphery and in the middle consisting of cells resembling stellate reticulum cells. False-negative results in the FNAB procedure can occur due to inadequate specimens or inaccurate sampling, mostly related to cystic tumors. To avoid this, FNAB tissue sampling can be performed at multiple sites and the deeper aspects of the tumor can assist in establishing an accurate preoperative diagnosis. Conclusion: The FNAB cytology is a reliable procedure for the pre-operative diagnosis of ameloblastoma. Pre-operative diagnosis of ameloblastoma can be used for planning therapy and early diagnosis of recurrence cases that can improve patient survival. The correlation between t